2018 AIAA Guidance, Navigation, and Control Conference 2018
DOI: 10.2514/6.2018-1605
|View full text |Cite
|
Sign up to set email alerts
|

Light Curve Analysis Using Wavelets

Abstract: A method is presented that uses wavelet decomposition in the analysis of light curves. Wavelet decomposition allows the frequency of a signal to be determined over time, and when applied to the light curve reflected by a space object, is used to determine the angular rate over time. This allows for detection in changes of the spacecraft's attitude state. Several cases of attitude maneuvers are presented, and the wavelet decomposition process is demonstrated using simulated and experimentally obtained data. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…This scaling function is time dependent and enables the temporal analysis. It has been previously shown that this temporal component enables wavelets to be used for assessment of SO attitude and rotation state changes [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…This scaling function is time dependent and enables the temporal analysis. It has been previously shown that this temporal component enables wavelets to be used for assessment of SO attitude and rotation state changes [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the use of hyperspectral technology and spectrometry have found important applications in astronomy, to classify and characterise asteroids [8] for example. In parallel, a body of work has focused on the use of light curve analysis to reconstruct the attitude motion or the shape of space objects [9][10][11][12][13][14]. More recently, Machine Learning (ML) was introduced to classify objects starting from their light curves [15,16].…”
Section: Introductionmentioning
confidence: 99%